Rich DeCoster letter to Nicholas S. Halmi, regarding bird sightings, March 1, 1978 and report for Iowa bird life - DeCoster, R. J. (Richard Joseph)et al (1978)
Letter from Rich DeCoster to Nicholas S. Halmi, regarding bird sightings, March 1, 1978, and report for Iowa Bird Life by Rich DeCoster, February 12, 1978.This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed